2001
DOI: 10.1212/wnl.56.7.861
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic impairment in painful neuropathy

Abstract: Autonomic symptoms in painful neuropathy are predominantly cholinergic and form a unique constellation of features that are distinct from other autonomic neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 28 publications
0
118
1
3
Order By: Relevance
“…Although the association with somatic autonomic neuropathy demands a more specific validation with quantitative sudomotor testing using the gold standard for sudomotor testing, Q-SART [22,23], this was not available in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association with somatic autonomic neuropathy demands a more specific validation with quantitative sudomotor testing using the gold standard for sudomotor testing, Q-SART [22,23], this was not available in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…7,[17][18][19] Several studies have demonstrated that QSART can determine sudomotor abnormalities with relatively high sensitivity and specificity in many types of polyneuropathies (Class II and III). [4][5][6][7]16,17,[19][20][21] In three Class III studies, QSART was shown capable of detecting distal small fiber polyneuropathy with a sensitivity of Ͼ75%. [17][18][19] Skin vasomotor reflexes assessed by monitoring skin blood flow using laser Doppler flowmeter have not been well studied.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…[4][5][6][7]16,17,[19][20][21] In three Class III studies, QSART was shown capable of detecting distal small fiber polyneuropathy with a sensitivity of Ͼ75%. [17][18][19] Skin vasomotor reflexes assessed by monitoring skin blood flow using laser Doppler flowmeter have not been well studied. Limited data from one Class III study using this technique demonstrated an unacceptably large coefficient of variation.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…The most useful tests are quantitative sudomotor axon reflex test (QSART), thermoregulatory sweat test, heart rate responses to deep breathing, Valsalva ratio, and surface skin temperature (Novak et al, 2001). The value of autonomic testing in patients with general neuropathic pain disorder, painful small-fiber neuropathy with burning feet has been shown in several studies.…”
Section: Autonomic Function Testingmentioning
confidence: 99%